Evaluation of the Implementation of the Puskesmas Information System (SIMPUS) Using the HOT-Fit Method at UPT Puskesmas Tirto Pekalongan City : Evaluasi Penerapan Sistem Informasi Puskesmas (SIMPUS) Menggunakan Metode HOT-Fit di UPT Puskesmas Tirto Kota Pekalongan - N.I, Ludvi Oktaviotika; N.W, Ayu Putri; Atmaliana, Santie; Mufida, Mufida; C.Y, Elan Surya (Procedia of Engineering and Life Science, 2025)
Puskesmas is a health service facility that carries out public health efforts and first-level individual health efforts, prioritizing promotive and preventive efforts in its working area. Puskesmas in carrying out effective and efficient health efforts requires health information that is organized through a cross-sector health information system. SIMPUS is a regional health information system program that provides information about all public health conditions at the community health center level, starting from personal data on patient, the availability of medicines, to public health education data. UPT Puskesmas Tirto used SIMPUS Indokes. Researchers conducted research using the HOT- Fit method to evaluate SIMPUS. This research uses quantitative methods with questionnaires. The research aims to evaluate the use of SIMPUS Indokes in improving the quality of health services at the UPT Puskesmas Tirto, Pekalongan City. Research on the four parameters of HOT-Fit : Humans, organization, technology and benefits related to the implementation of the SIMPUS Indokes program at the UPT Puskesmas Tirto, shows good results so that it can be continued and developed according to service needs at the puskesmas, but there must still be human resources who continue to be trained when ever the information is always up to date.